Perbandingan Hasil Pemeriksaan Demam Tifoid Menggunakan Metode Widal Slide Dan Metode Rapid Test IgG IgM Di RSUD Dr R Goeteng Taroenadibrata - Brilianto, Samuel Surya; Mulyanto, Arif; Sulistyowati, Retno; Rahaju, Minto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Typhoid fever is an acute infection of the small intestine caused by the bacteria S. typhi and S. paratyphi. This study aims to evaluate the results of typhoid fever testing using the Widal slide method and the Rapid test IgG IgM method at Dr. R. Goeteng Taroenadibrata Hospital in Purbalingga. Conducted in May 2024 with an observational analytic design and a cross-sectional approach, the sample consisted of 18 patients with typhoid fever. Widal slide examination results using O antigen reagent at RSUD dr. R.Goeteng Taroenadibrata, Purbalingga Regency, there titer 1/160 from 16 respondents (100%). Results of the IgG IgM Rapid test using O antigen at RSUD dr. R. Goeteng Taroenadibrata, Purbalingga Regency, there were 13 respondents (81.2%) IgG negative cases, 3 respondents (18.8%) had IgG positive cases, and 3 respondents (18.8%) had IgM negative cases, 13 IgM positive cases. respondents (81.2%). There was no difference in the results of the Widal slide examination and the Rapid IgG IgM test using O antigen in respondents at RSUD dr. R. Goeteng Taroenadibrata, Purbalingga Regency with p rate = 0.01 (P= < 0.05). Similarly, Fisher's test for IgG IgM yielded a P value of 0.04, So it can be concluded that there is a difference in the results of the Widal slide examination and the results of the IgM Rapid test.